Assistance in Financial Management for SMEs in the Gresik Region - Rusdiyanto, Rusdiyanto; Setyorini, Haryati; Suharto, Suharto; Syamlan, Adiba Fuad; Pramitasari, Dini Ayu; Ulum, Bustanul; Burhan, Umar; Sundari, Sri; Syafii, Mochamad; Hasanah, Anisaul; Tuharea, Firdaus Indrajaya; Ilham, Rachmad (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2024)
In an era where micro, small, and medium-sized businesses are developing and growing, proficiency in SMEs' financial reporting management is becoming increasingly important. This expansion is not unrelated to Indonesia's micro, small, and medium-sized enterprise (SMEs) growth, which is primarily concentrated in the Greek district and keeps growing every year. The supporting activities and training management of the financial report presentation of micro, small, and medium-sized enterprises SMEs in the village of Semampir, Cerme district of Gresik, are described in this article. This course aims to assist SMEs (micro, small, and medium-sized businesses) in becoming more proficient in handling financial reporting. The recording of financial transactions about cash inputs and cash outputs, the division of personal and corporate finances, financial protection, and financial planning are the four key topics covered in the supporting and training materials. In SMEs